2018
DOI: 10.1136/gutjnl-2018-317057
|View full text |Cite
|
Sign up to set email alerts
|

Identifying optimal candidates for early TIPS among patients with cirrhosis and acute variceal bleeding: a multicentre observational study

Abstract: ObjectivesEarly placement of transjugular intrahepatic portosystemic shunt (TIPS) has been shown to improve survival in high-risk patients (Child-Pugh B plus active bleeding at endoscopy or Child-Pugh C 10–13) with cirrhosis and acute variceal bleeding (AVB). However, early TIPS criteria may overestimate the mortality risk in a significant proportion of patients, and the survival benefit conferred by early TIPS in such patients has been questioned. Alternative criteria have been proposed to refine the criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 40 publications
5
148
1
2
Order By: Relevance
“…Therefore, there may be an added role of NSBBs in the prevention of ACLF beyond just decreasing variceal hemorrhage . Also, preemptive TIPS in patients with Child C (≤13 points) seems to have a survival benefit . The mechanism of this protective effect is not clear, but given that ACLF is the strongest negative predictor for survival among patients with a GI bleed, there is suspicion that TIPS may prevent the development of ACLF .…”
Section: Gi Hemorrhagementioning
confidence: 99%
“…Therefore, there may be an added role of NSBBs in the prevention of ACLF beyond just decreasing variceal hemorrhage . Also, preemptive TIPS in patients with Child C (≤13 points) seems to have a survival benefit . The mechanism of this protective effect is not clear, but given that ACLF is the strongest negative predictor for survival among patients with a GI bleed, there is suspicion that TIPS may prevent the development of ACLF .…”
Section: Gi Hemorrhagementioning
confidence: 99%
“…[4][5][6] However, propranolol could only lower the level of HVPG by 10.1-23.2%, carvedilol by 18.6-27.7%. 8,9 TIPS is well known for significantly decreasing the level of PPG, 10,11 which is only considered as the treatment of choice when the first-line therapy failed currently. 2 Therefore, for patients with PPG ≥ 25 mmHg, neither EVL nor NSBB therapy is effective in reducing the mortality of them, even postpone the optimal timing of transjugular intrahepatic portosystemic shunt (TIPS) implantation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, for patients with PPG ≥ 25 mmHg, neither EVL nor NSBB therapy is effective in reducing the mortality of them, even postpone the optimal timing of transjugular intrahepatic portosystemic shunt (TIPS) implantation. 8,9 TIPS is well known for significantly decreasing the level of PPG, 10,11 which is only considered as the treatment of choice when the first-line therapy failed currently. For patients with PPG ≥ 25 mmHg who have high risk of treatment failure and mortality, however, the primary goal should be reducing the level of PPG, which inspires the idea that maybe we should apply TIPS as the first-line therapy on this kind of patients to prevent variceal rehemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent Chinese multicenter observational study recently confirmed our data and demonstrated the survival benefit of Child-Pugh C (<14 points) patients admitted with acute variceal bleeding. (1) Of note, the metanalysis mentioned by Lo et al showed a trend toward a better survival in Child-Pugh C patients (odds ratio = 0.34; 95% confidence interval [CI] = 0.10-1.11; P = 0.074), despite a high heterogeneity between studies (P = 0.06; I 2 = 60%), suggesting that these data should be interpreted with caution. Indeed, when examining carefully the data, the study disagreeing the most was retrospective, using historical controls (that may have a different risk) and with a more permissive high-risk definition.…”
Section: Replymentioning
confidence: 94%
“…Acute and chronic variants of AIH exhibit variable degrees of fibrosis (stages I-IV) despite significant differences in the pattern of necroinflammation. (1) Diagnosing AIH in a patient presenting with first acute decompensation with no known history of cirrhosis is quite challenging. It may represent acute decompensation of previously undiagnosed compensated cirrhosis precipitated by extrahepatic bacterial infection, systemic inflammatory response syndrome (SIRS), alcohol consumption, drugs, toxins, or acute viral hepatitis.…”
Section: To the Editormentioning
confidence: 99%